Effectiveness of entomopathogenic fungi against peach fruit fly, Bactrocera zonata (Saunders) (Tephritidae: Diptera) - Javed, Ushna; Ahmad, Shahbaz; Ashfaq, Muhammad; Iqbal, Mubashar; Chattha, Muhammad Bilal; Javaid, Arshad; Sarwar, Mubeen; Shafeeq, Tahir (Journal of Agriculture and Biology, 2024)
Bactrocera zonata, commonly known as peach fruit fly, attacks a number of soft fruits such as peach, guava and mango.  For its control, entomopathogenic fungi offer a safe and efficient substitute of insecticides, which can lead to pest resistance and environmental pollution. In the present study, four entomopathogenic fungi namely Beauveria bassiana, Metarhizium anisopliae, Trichoderma harzianum and Verticillium lecanii were tested against male and female adults of B. zonata through in vitro contact bioassay at concentrations of 1×104, 1×106, 1×108, 1×1010, and 1×1012 cfu/ml. Mortality of B. zonata was recorded at 3, 7, 10 and 14-day post-exposure intervals. Results showed that as the concentration of spore/condial suspension of B. bassiana, M. anisopliae, V. lecanii and T. harzianum was increased from 1.0 × 104 to 1.0 × 1012 cfu/ml, LT50 values were decreased from 20.45 to 8.40 , 62.85 to 16.68, 62.85 to 16.68, and 34.09 to 16.42 days for female, and 23.82 to 9.1, 63.80 to 12.65, 63.80 to 12.65 and 29.55 to 13.90 days for male B. zonata, respectively. LC50 values of B. bassiana, M. anisopliae, V. lecanii and T. harzianum against B. zonata decreased from 5.17 × 1016 to 6.36 × 108, 9.33 × 1013 to 5.58 × 109, 3.02 × 1015 to 8.07 × 1011and 4.00 × 1018 to 6.80 × 1013 cfu/ml  for female, and from 2.60 × 1015 to 3.03 × 108, 2.26 × 1014 to 1.13 × 109, 3.73 × 1015 to 7.04 × 1010 and 2.67 × 1019 to 1.02 × 1012  cfu/ml for male, respectively, over a period of 3–14 days. On the 14th day, B. zonata males had the highest mortality (84%) due to B. bassiana at 1×1012 cfu/ml, followed by 48%, 59% and 74% mortality due to T. harzianum, V. lecanii and M. anisopliae, respectively. In general, adult female mortality was lower than the adult male mortality. With a moderate to high mortality of B. zonata due to different fungal species, the findings of the present study show that the tested entomopathogenic fungi are highly effective in controlling this pest. Because of their high efficacy against B. zonata, the two fungal species viz. B. bassiana and M. anisopliae can be included in an IPM plan to control B. zonata.
Keywords: Bactrocera zonata; Beauveria bassiana; Metarhizium anisopliae; Trichoderma harzianum; Verticillium lecanii; Mortality